Pemberdayaan Perempuan Desa Melalui Pelatihan Bakpao Ubi Kuning dalam Meningkatkan Kreativitas Olahan Pangan Lokal di Desa Sambirejo, Kecamatan Ngrambe, Kabupaten Ngawi (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to empower rural women through training in making steamed buns (bakpao) using yellow sweet potatoes in Sambirejo Village, Ngrambe District, Ngawi Regency. Yellow sweet potatoes are one of the abundant local agricultural products, yet their utilization has been limited to household consumption. Through this program, yellow sweet potatoes were processed into innovative food products in the form of bakpao, which provide nutritional value, consumer appeal, and economic opportunities. The method applied was Asset Based Community Development (ABCD) with a participatory approach, emphasizing the use of local assets and the active involvement of community members. The stages included asset identification, technical training through demonstration, hands-on practice, and evaluation. Participants were drawn from PKK women and local micro, small, and medium enterprises (MSMEs). The results showed significant improvements in participants’ knowledge of local food diversification, technical skills in processing yellow sweet potatoes, and entrepreneurial motivation to initiate home-based businesses. In addition, the training encouraged participants’ creativity in developing more varied local food products. Therefore, the program not only contributed to women’s empowerment but also strengthened MSMEs, promoted local food innovation, and supported community economic independence.